Analysis of Candidate Genes in Occurrence and Growth of Colorectal Adenomas. (29th October 2009) - Olschwang, Sylviane; Vernerey, Déwi; Cottet, Vanessa; Pariente, Alexandre; Nalet, Bernard; Lafon, Jacques; Faivre, Jean; Laurent-Puig, Pierre; Bonithon-Kopp, Claire; Bonaiti-Pellié, Catherine
Abstract : Predisposition to sporadic colorectal tumours is influenced by genes with minor phenotypic effects. A case-control study was set up on 295 patients treated for a large adenoma matched with polyp-free individuals on gender, age, and geographic origin in a 1 : 2 proportion. A second group of 302 patients treated for a small adenoma was also characterized to distinguish effects on adenoma occurrence and growth. We focussed the study on 38 single nucleotide polymorphisms (SNPs) encompassing 14 genes involved in colorectal carcinogenesis. Effect of SNPs was tested using unconditional logistic regression. Comparisons were made for haplotypes within a given gene and for biologically relevant genes combinations using the combination test. The APC p.Glu1317Gly variant appeared to influence the adenoma growth (P = .04, exact test) but not its occurrence. This result needs to be replicated and genome-wide association studies may be necessary to fully identify low-penetrance alleles involved in early stages of colorectal tumorigenesis.